(untitled) (Revista Brasileira Multidisciplinar, 2024)
Sinusitis is an infection of the maxillary sinus membrane with a relatively high incidence. Etiologic factors include periapical and/or periodontal disease in upper posterior teeth in close contact with the maxillary sinus. Treatment should be multidisciplinary, addressing therapy with antibiotics, decongestants, removal of the causal factor, and if necessary, drainage of the purulent collection. Thus, the objective of this study was to report a case of unilateral paranasal sinusitis with multidisciplinary treatment, contributing to the guidance of professionals regarding the diagnosis and appropriate therapy. Patient MFN, female, 58 years old, without systemic alterations, attended the clinic reporting having undergone an antrotomy in order to treat sinusitis, but without success. She complained of pain, fever, halitosis, rhinorrhea and nasal obstruction. The intraoral clinical examination revealed the presence of a periodontal pocket on teeth 26 and 27, with an active inflammatory process. The tomographic examination showed veiling of the left maxillary sinus, with thickening of the mucosa. The diagnosis was unilateral odontogenic sinusitis and the treatment was the extraction of teeth 26 and 27, followed by closure of the oroantral communication, which was performed using a mucoperiosteal flap associated with the buccal fat pad. The patient had a good recovery, with healing of the ridge without communication with the maxillary sinus, and had relief of the symptoms of sinusitis. Thus, it was concluded that patients with unilateral paranasal sinusitis should be examined clinically and through imaging tests to identify dental pathologies associated with maxillary sinus diseases.